Hepatocellular Carcinoma: A Cross-Sectional Analysis of Risk Factors - Faisal Naeem Bandesha, Shoaib Anwar, Kanza Ilyas Rehan, Amna Shahid, Rida Khalid, Ayesha Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background Hepatocellular carcinoma is the most prevalent primary liver cancer globally and the major cause of cancer-associated deaths. Method: A cross-sectional study was carried out at CMH Multan’s Department of Histopathology. The individuals with HCC presented to CMH Multan’s OPD or indoor general medicine department were selected. Informed consent was obtained. On a standardised proforma, all information such as gender, age groups, residence status, family history, diabetes, smoking, hypertension, and obesity was entered and analysed using the latest version of the SPSS. Results: 85 (67.5%) of the 126 study cases were male, whereas 41 (32.5%) were female. 72 (57.1%) were from metropolitan areas, while 54 (42.9%) were from rural areas. Smoking was found in 10 (7.9%), and diabetes was found in 43. (34.1%). Obesity was found in 18 (14.3%), and hypertension was present in 74 (58.7%). Only 5 (4%) of our study cases had a family history of HCC. Conclusion: HCC is more common in male patients, older patients, urban patients, and patients with diabetes, hypertension, and obesity. Individuals with diabetes, hypertension, and obesity undergo screening for HCC regularly. Further research is necessary to recognise the environmental and genetic variables that could contribute to developing HCC in various environments and populations. Keywords: Liver, Risk factors, Hepatocellular carcinoma, Liver neoplasms.